Simple new correlation for the prediction of equilibrium constant (KP) of Haber reaction covering the industrial conditions - Muhammad Mahmoud El-Gharbawy; Fatma Khalifa Gad; Walaa Mahmoud Shehata (Egyptian Journal of Petroleum)
Ammonia is an important industrial chemical, and its production is one of the highest of all inorganic chemicals. It is synthesized, in principal, from nitrogen and hydrogen by Haber process. It was found that the equilibrium constant (KP) of Haber reaction is strongly pressure dependent. Many correlations were developed in order to rigorously express this (KP); however, the most reliable expressions involved are inherently complex. This paper illustrates a simple correlation which was developed to express the value of (KP) of Haber reaction at temperatures from 350 to 600 °C and pressures from 50 to 300 atm, which covers today’s industrial range. In this correlation, KP is expressed in terms of temperature and pressure of equilibrium mixture which is the direct data measured. The effects of temperature and pressure are not separated allowing KP to be calculated directly, without iterations; using spreadsheet. Results were compared to that of Gillespie and Beattie method showing very good match. The new simple correlation can be used easily in commercial simulation packages, e.g. Hysys, using its embedded spreadsheet to build reliable ammonia synthesis reactor modeling benefiting from featured analysis methods of these packages.